New Antibacterial and 5-Lipoxygenase Activities of Synthetic Benzyl Phenyl Ketones: Biological and Docking Studies - Sepulveda-Boza, S; Espinosa-Ferrada, V; Montoya-Kunsting, M; Mascayano-Collado, C; Vasquez-Martinez, y; Cortez-San Martin, M; Mejías-Medina, S; Cabezas-Gómez, F; Torrent-Farias, C (Academic Press, 2019)
We investigated twelve benzyl phenyl ketone derivatives which are synthetic precursors of isoflavonoids that are shown be good 5-hLOX inhibitors, especially those that have the catechol group, but these precursors never have been assayed as 5-hLOX inhibitors being a novelty as inhibitors of the enzyme, due to sharing important structural characteristics. Screening assays, half maximal inhibitory concentration (IC50) and kinetic assays of all the studied molecules (5 µg/ml in media assay) showed that 1-(2,4-dihydroxy-3-methylphenyl)-2-(3-chlorophenyl)-ethanone (K205; IC50 = 3.5 µM; Ki = 4.8 µM) and 1-(2,4-dihydroxy-3-methylphenyl)-2-(2-nitrophenyl)-ethanone (K206; IC50 = 2.3 µM; Ki = 0.7 µM) were potent, selective, competitive and nonredox inhibitors of 5-hLOX. Antioxidant behavior was also assayed by DPPH, FRAP, and assessing ROS production, and those with antibacterial and antiproliferative properties relating to 1-(2,4-dihydroxy-3-methylphenyl)-2-(2-chlorophenyl)-ethanone (K208) established it as the most interesting and relevant compound studied, as it showed nearly 100% inhibition of bacterial growth of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Finally, docking studies were done that helped to characterize how the inhibitor structures correlated to decreased 5-hLOX activity. © 2018 Elsevier Inc.